FORMATION AND MORPHOLOGY OF PHOSPHORUS AND NICKEL IMPURITY ATOM CLUSTERS IN SILICON DURING SEQUENTIAL DOPING AND THERMAL ANNEALING (Web of Technology: Multidimensional Research Journal, 2024)
This study investigates the effect of sequential doping of silicon with phosphorus and nickel on the formation, size, and morphology of impurity clusters. P-type silicon wafers obtained by the Czochralski method were subjected to phosphorus diffusion to form a p-n junction, followed by nickel deposition and high-temperature diffusion, with a final thermal annealing process. The resulting cluster structures were analyzed using scanning electron microscopy (SEM). The formation of precipitates of various shapes and sizes was observed, including oval and round clusters ranging from nanometers to several micrometers. A correlation between technological process parameters and the characteristics of the formed clusters was established. The results enhance the understanding of impurity atom interactions in silicon and open prospects for developing new methods for controlled impurity structure formation